PENGAWASAN KEIMIGRASIAN TERHADAP ORANG ASING OLEH KANTOR IMIGRASI KELAS II DUMAI MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN - TIMBUL AMAN SIMORANGKIR; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Immigration comes from Dutch, Immigratie. Immigratie means someone who leaves his/her country by him/her self to stay or go to another country. Law of Immigration talk about people who are come to Indonesia and go out from Indonesia. Dumai city is a strategy place because it is near to Malaysia. It means that foreigners can come Indonesia or go out from Indonesia. That foreigners usually come to Indonesia to get a job, enjoy their vacation or just for transit. That strategy place make foreigners to come to Dumai illegality. They don’t have a document so they come in to the small ports which is place at the harbor of beach. In fact, there are a lot of foreigners have a job in Dumai but they don’t have document which is haven’t an extension document. They are a criminal of immigration. To ge a good stability and nation importance, nation sovereignty, security, general discipline and alert to the negatie possibility of come in or go out, existence, and foreigners activity in Indonesia, so Indonesia need to make a rule about controlling foreigners and immigration activity. As article 66 verse 2 Law of the republic of Indonesia number 6 of 20112011 concerning immigration says that the alert of foreigners like alert of foreigners who come in and go out, and alert of existence and foreigners activity in Indonesia..Keyword: Supervision - Immigration - Foreigners